108k views
4 votes
NEED HELP ASAP !!!

Simplify -6^2 ÷ 12 - 2(-7).

17
35
11
-35

User Copper
by
5.5k points

2 Answers

6 votes

Answer:

17

Explanation:

-6² ÷ 12 - 2(-7)

-36 ÷ 12 - 2(-7)

-36 ÷ 12 + 14

-3 + 14

= 11

User Andylei
by
6.8k points
3 votes

Answer:

Option 3 -
-6^2/ 12-2(-7)=11

Explanation:

Given : Expression
-6^2/ 12-2(-7)

To find : Simplify the expression ?

Solution :

Expression
-6^2/ 12-2(-7)


-6^2/ 12-2(-7)=-36/ 12-2(-7)


-6^2/ 12-2(-7)=-(36)/(12)+14


-6^2/ 12-2(-7)=-3+14


-6^2/ 12-2(-7)=11

Therefore, the expression is
-6^2/ 12-2(-7)=11

So, Option 3 is correct.

User KoalaZub
by
6.5k points